UNDERSTANDING EMPLOYEE BURNOUT: CAUSES, CONSEQUENCES, AND PREVENTION STRATEGIES - Myint, Aung; Hlaing, Nandar; Pradhan, Kiran (Research Psychologie, Orientation et Conseil, 2026)
Employee burnout has become a significant concern for organizations worldwide, affecting both individual well-being and organizational productivity. Characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, burnout can lead to severe consequences such as increased absenteeism, decreased performance, and higher turnover rates. This study aims to examine the causes, consequences, and prevention strategies of employee burnout. The research explores the psychological, organizational, and environmental factors that contribute to burnout and investigates the impact of burnout on employee well-being and organizational outcomes. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 300 employees across various industries, using established scales to measure burnout, job satisfaction, and organizational commitment. The qualitative interviews provided deeper insights into personal experiences and the workplace factors contributing to burnout. The findings revealed that work overload, lack of control, and insufficient support were the primary causes of burnout. Burnout was found to significantly affect employee well-being, leading to increased stress, anxiety, and decreased job satisfaction. Prevention strategies, such as workload management and organizational support, were identified as effective in reducing burnout.